COMPARATIVE PRODUCTIVE PERFORMANCE OF BEETAL GOATS IN ANNUAL AND ACCELERATED SYSTEM - N. Ahmad; K. Javed; M. Abdullah; A. S. Hashmi A. Ali; Z. Iqbal; U. Younas; Z. M. Iqbal (Journal of Animal and Plant Sciences, 2014)
Fifty adult Beetal goats were divided into two groups viz. accelerated kidding and annual kidding having 25 animals each. Each group was further divided into 5 sub-groups, 5 animals in each and considered as replicate. The accelerated kidding group produced three crops where as the annual breeding group produced two crops. Birth weight of kids produced in three different seasons of March-April, 2010; October-November, 2010 and June-July, 2011 were as 2.85±0.13, 3.32±0.40 and 3.29±0.31 kg as compared to kid crop produced in annual kidding system showing birth weight as 3.09±0.16 kg and 3.08±0.16 kg, respectively. The average body weight at 3 months of age of first, second and third kid crop in accelerated kidding system was noticed as 12.72±2.29, 11.31±0.98 and 11.44±1.60 kg, respectively as compared to 11.82 and 11.81 kg in annual kidding system. In order to minimize the gap of animal protein in human food, strategies like accelerated kidding may be adopted which might satisfy nutritional demands. The growth rate at 3 months age of  two kid crops of annual and three kid crops of accelerated systems were observed as 97.00±2.54, 71.67±2.08, 109.44±5.83, 88.71±2.17 and 90.45±3.75gms, respectively. Whereas, at 6 months age of two kid crops of annual and three kid crops of accelerated systems, the growth rate was observed as 93.56±2.27, 110.71±0.94, 105.78±4.05, 109.86±1.03 and 109.64 ±1.26gms, respectively. The growth rate of two kid crops of annual and three kid crops of accelerated systems  was 66.64 ±1.42, 91.22 ±2.74, 67.00 ±0.48, 67.57 ±2.72 and 67.73 ±6.08gms at 9 months of age, respectively.
Keywords: annual kidding; accelerated kidding; Beetal goats; birth weight; weight gain